Preliminary Observations on Fish Biodiversity and Some Limno-chemical Parameters of Ichhamati Estuary, Sundarbans, West Bengal - Ghosh, Amitabha; Satpathy, B B (Journal of the Inland Fisheries Society of India, 2020)
The Sundarbans, the largest delta of the world, is endowed with a large number of intermingling tidal channels constituting the Sundarbans estuarine complex, which provides food and shelter for different life cycle stages of a large number of fish species. The Indian part of this largest mangrove forest is situated in the districts of 24-Parganas North and South, in the state of West Bengal. The river Ichhamati, the lower most part of a right bank distributary (Mathabhanga river) of Padma branch of the river Ganga, is an international and trans-border river meandering through India and Bangladesh and forming border at places between these two countries. After finally entering into the North 24-Parganas district of West Bengal, Ichhamati falls into the Kalindi-Raimangal -Hariabhanga (Herobhanga) estuarine complex and ultimately drain into Bay of Bengal. This river forms the eastern most boundary of theIndian part of the Sundarbans. The estuarine span of the river from Hingalgunj to little above Basirhaat isaround 50 km or so. A large number of estuarine wetlands, situated in the vicinity of Ichhamati, are dependent on this estuary for water supply and fish seed, entering into those wetlands along with ingress water. The estuary is in a criticalcondition due to siltation, weed chocking at places and various anthropogenic interferences.